Cytohistological Correlation in Pleural Effusions Based on the International System for Reporting Serous Fluid Cytopathology - Daniel Pinto; Eduardo Cruz; Diamantina Branco; Cláudia Linares; Conceição Carvalho; Amélia Silva; Martinha Chorão; Fernando Schmitt (Diagnostics, 2021)
The International System for Reporting Serous Fluid Cytology (TIS) was recently developed. Given its novelty, most studies looking into the risk of malignancy (ROM) of serous effusion diagnostic categories were published before the development of TIS. We searched the database of our department for pleural effusions diagnosed in the last five years, excluding those without a corresponding pleural biopsy. Cases were reviewed and reclassified according to the TIS. A cytohistological correlation was performed. In total, 350 pleural effusion specimens with one or more corresponding pleural biopsies were included. After reclassification, 5 (1.43%) were nondiagnostic (ND), 253 (72.29%) were negative for malignancy (NFM), 7 (2.00%) had atypia of unknown significance (AUS), 14 (4.00%) were suspicious for malignancy (SFM), and 71 (20.57%) were malignant (MAL). Calculated ROM was 40% for ND, 20.16% for NFM, 42.86% for AUS, 78.57% for SFM, and 100% for MAL. Effusion cytology sensitivity and specificity were 60.29% and 98.56%, respectively. This is the first publication looking into the cytohistological correlation of a retrospective cohort of pleural effusions based on the TIS. We add to the body of data regarding the ROM for TIS categories, highlighting areas of potential future research.